Analysis of expert`s opinion of optimal beginning age for learning technical skills in water polo - Hraste, M.; Jelaska, I.; Clark, C. C. (Acta Kinesiologica, 2023)
Purpose: Optimizing the training process of young water polo players according to children's developmental characteristics and didactic principles is of pivotal importance; however, there is a lack of research in the area. Therefore, we sought to determine and explain the appropriate age for beginning of learning technical elements in water polo according to water polo experts` coaches` opinion.